ANTI-CATARACT ACTIVITY OF GARCINIA INDICA AGAINST NAPHTHALENE-INDUCED CATARACT IN RATS - Patel, Milap R; Bg, Patel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate the anti-cataract activity of the aqueous extract of Garcinia indica (AGI) fruit rinds on naphthalene-induced cataract using rats. Methods: Anti-cataract activity of AGI was evaluated using naphthalene model. Rats were divided into five groups (n=6 in each). Naphthalene solution was prepared by dissolving naphthalene in warm corn oil and administered at the dose of 0.5 g/kg/day p.o. for first 3 days and 1 g/kg/day p.o. thereafter for the induction of cataract. Group I normal control received corn oil 5 ml/kg/day. Group II cataract control received naphthalene solution. Group III received Vitamin E 50 mg/kg/day p.o., and Groups IV and V received AGI 200 mg/kg/day p.o and 400 mg/kg/day p.o., respectively, along with the naphthalene solution for 28 days. At the end of the treatment, levels of malondialdehyde, lipid hydroperoxides (LH), carbonyl and sulfhydryl content, and enzymatic and non-enzymatic antioxidants in lens homogenate were measured. Results: Administration of naphthalene produced a mature cataract and an increase in the opacity index. A significant increase in LH and protein carbonyl content while decrease in protein SH content and antioxidant enzymes was found in naphthalene control group as compared to normal control group. Simultaneous administration of AGI and naphthalene delayed the onset and maturation of cataract. Conclusion: The present investigation suggests that AGI protected the lens against naphthalene-induced oxidative damage which might be responsible for delaying the progression of cataract.